A NUMERICAL STUDY ON THE INFLUENCES OF URBAN PLANNING AND CONSTRUCTION ON THE SUMMER URBAN HEAT ISLAND IN THE METROPOLIS OF SHENZHEN - 张小丽 李磊 杜雁 江崟 房小怡 力梅 陈元昭 白玉洁 (Journal of Tropical Meteorology, 2011)
By means of the regional boundary layer model （RBLM）,a study on the influences of the urban planning and construction on the summer urban heat island （UHI） in the metropolis of Shenzhen is performed.In the study,the current summer UHI distribution,the influences of the increasing high-density construction and the energy consumption on the summer air temperature distribution,and the influences of the urban ventilation corridor on the summer air temperature distribution are numerically analyzed.Some conclusions are drawn in the light of the study：（1） The summer UHI is more obvious in day time than that in night time in the summer of Shenzhen,and the maximum values of UHI intensity in the day time appear in the areas with high-density construction,which are located in Nanshan,Futian and Luohu and western Bao＇an districts.（2） The increase of construction density and energy consumption in the urban area will lead to the increase of temperature near the ground,and the increase of temperature at nighttime is more obvious than that at daytime.（3） The ventilation corridor can effectively reduce the UHI intensity and can be taken as a method to eliminate the negative climatic effect caused by the increase of high-density construction and energy consumption in the future.